AB0439 LUNG FINDINGS IN PATIENTS WITH PRIMARY SJOGREN'S SYNDROME. (2nd June 2020) - Özdemir Işik, Ö.; Yazici, A.; Cefle, A.
Abstract : Background: Sjogren's syndrome (SS) is a systemic, autoimmune disease and can affect many organs and systems. Objectives: In this study, we planned to present the lung findings of primary SS (pSS) patients who are being followed in our outpatient clinic. Methods: Chest radiographs and thorax CTs of 151 patients who were admitted to the rheumatology outpatient clinic between 2004 and 2017 and diagnosed as pSS according to the classification criteria of the American-European consensus group Sjogren's syndrome were retrospectively scanned. Results: In our study, 97% of pSS patients were female and 3% were male and the mean age was 56 ± 12 years, disease duration was 10.5 ± 5 years. It was observed dry eye in 86% of patients, dry mouth in 88%, parotitis in 17%, arthritis in 29%, vasculitis in 4%, neuropathy in 6%, myositis in 1%, lymphadenopathy in 29% (LAP), and 20% of patients had Raynaud phenomenon. In 50% of the patients, chest radiography was normal, and there were no respiratory complaints. Thorax CT was requested due to suspicious appearance on 50% chest x-ray. According to CT findings, 23% had nodules in the lung, nodule sizes were less than 1 cm, and patients were followed up for an increase in size. Hiler and subcarinal lymph nodes were present in 6% of patients and their sizes was ranged from 5 mm to 15 mm. Bronchoscopy was performed for two patients due to mediastinal LAP. Biopsy results were evaluated as reactive changes. Interstitial lung disease (ILD) findings were present in 16 patients. (69% NSIP, 25% LIP, 6% UIP). All patients with ILD received steroid therapy. Two patients received 6 cycles of cyclophosphamide treatment for active alveolitis and azathioprine (AZA) was used in maintenance therapy. Due to ILD, one patient was receiving rituksimab, one patient was receiving mycophenolate mofetil, while nine patients were using AZA. It was found bronchiectasis in 3% of patients, emphysema in 5%, sequelae fibrotic changes in 13%, and 1% patients had thickening of the pleura. One patient was diagnosed with hypersensitivity pneumonia and two patients had lung cancer (Table-1). There was a smoking history in 21% of the patients. There was a significant relationship between smoking and development of emphysema and malignancy. The relationship between smoking and lung cancer development could not be assessed due to the absence of lung cancer in the non-smoking group (Table-2). Conclusion: Lung findings are detected in 9-12% of patients in pSS, which can increase to 75% with the use of tomography, pulmonary function tests and bronchoscopy. Since pSS has a wide spectrum from airway disease or interstitial lung disease to BALT lymphoma lung involvement of the disease has been emphasized. References: [1]Hatron PY, Tillie-Leblond I, Launay D, et al.: Pulmonary manifestations of Sjogren's syndrome. Presse Med. 40:e49-e64 2011 Disclosure of Interests: None declared